Relationship between ventilatory threshold and muscle fiber conduction velocity responses in trained cyclists - Cardoso Pereira, M. C.; de Araújo Rocha Júnior, V.; Bottaro, M.; Monteiro de Andrade, M.; Peruzzo Schwartz, F.; Martorelli, A.; Celes, R.; Carvalho Carmo, J. (Journal of Electromyography and Kinesiology, 2013)
The relationship between surface electromyography (SEMG) amplitude and the ventilatory threshold has been extensively studied. However, previous studies of muscle fiber conduction velocity (MFCV) are scarce and present insufficient evidence concerning the relationship between MFCV and metabolic responses during cycling. Based on that fact, the purpose of this study is twofold: (1) to investigate the existence of a MFCV threshold (MFCVT) during cycling and (2) to verify if this possible breakpoint is correlated with the ventilatory threshold (VT) and the SEMG threshold (SEMGT). Eight trained male cyclists (age 36.0 ± 9.7 years) performed an incremental cycling test with initial workload of 150 W gradually incremented by 20 W min-1 until the exhaustion. Gas analyses were conducted using a breath-by-breath open-circuit spirometry and SEMG were registered from vastus lateralis in each pedaling cycle with a linear array of electrodes. A bi-segmental linear regression computer algorithm was used to estimate VT, MFCVT and SEMGT respectively in the carbon dioxide production (VCO2), MFCV and electromyography root mean square (EMG RMS) curves. The one way ANOVA for repeated measures did not reveal any significant difference among VT (77.1 ± 7.5% of VO2max), MFCVT (80.3 ± 10.4% of VO2max) and SEMGT (81.9 ± 11.7% of VO2max). The Bland and Altman procedure confirmed a good concordance between SEMGT and VT (Bias = 5.5 of %VO2max) as well as MFCVT and VT (Bias = 5.2 of %VO2max). The present findings suggest that muscle fiber conduction velocity threshold is a valid and reliable non-invasive tool to obtain information about ventilatory threshold in trained cyclists.